Nutrient Saving and Yield Enhancement through Fertigation in Apple-Growing Cold Humid Regions of North-west Himalayas - O.C. Sharma, J. I. Mir, D.B. Singh, Wasim H. Raja and Sanjay Arora, Anil Sharma, Sarvendra Kumar Shiv Lal, Geetika Malik (Journal of the Indian Society of Soil Science, 2018)
In order to identify suitable fertigation techniques to get higher return from fertilizer application in applegrowingcold humid regions of north-west Himalayas, an experiment with different fertigation treatmentswas conducted at ICAR-Central Institute of Temperate Horticulture Farm, Srinagar. As regards yieldfertilizerratio (YFR), the results suggested superiority of three fertigation treatments viz. 50% recommendedfertilizer (RF) in one split, 50% RF in two splits and 75% RF in two splits over other treatments with valueof YFR being 16.0, 15.7 and 14.3, respectively. Apple leaves and fruits exhibited highest macronutrientcontent with the application of 100% RF dosage in two splits. Results revealed that 25% of the RF could besaved along with increase in apple fruit yield on applying 75% of the RF in two splits through fertigation.The maximum apple yield, nutrient accumulation efficiency, macronutrient concentration in leaf and fruitswas also observed in the aforesaid treatment.